IDENTIFIKASI GERAKAN TANAH DI DESA KEBONHARJO DAN SEKITARNYA, KABUPATEN KULON PROGO, YOGYAKARTA: THE IDENTIFICATION OF SOIL MOVEMENT IN KEBONHARJO AND NEIGHBORHOODS, KULON PROGO REGENCY, YOGYAKARTA - Ade Tiyas Nurhaja Tiyas; Suherman Dwi Nuryana; Muhammad Adimas Amri (Universitas trisakti, 2022)
The village of Kebonharjo and neighborhoods is zone of relatively high ground movement. In the western part of Indonesia, it was formed due to the influence of the collision two tectonic plates. Kebonharjo and neighborhoods are earthquake and volcanic zone. With a steep slope and high rainfall data, one of the biggest factors for landslides. This study aims to fins out what potential couse the area to become a landslide-prone area and there indications of anything in the research area. There are several obstacles to the development of the Kebonharjo village are and suggroundings. In its study using the DVMBG method qhich combines several parameters, on of which is rainfall parameter data, geology, slope, land use and soil types. The potential for landslides in Kebonharjo village really needs attention because the are is very high and the rainfall is high, the potential for large landslides. After counducting the research, it can be seen the types of landslides according to (Varnes, 1978), type of landslides Earth Spread and Earth Flow. Keywords: Soil Movement, DVMBG method, tectonic.